Challenges in Implementing Values-Based Education: A Qualitative Study at Sekolah Terpadu Musa-Asiah (Sepama), Cambodia - Aminas, L.Y.; Musa, Mohamad Zain; Ahmad (International Journal of Learning Reformation in Elementary Education, 2025)
This qualitative study explores the challenges of implementing values-based education in Sekolah Terpadu Musa-Asiah (Sepama), an integrated Islamic elementary school in Svay Khleang Village, Kroch Chmar District, Thbong Khmum Province, Cambodia. Using observation and interviews with teachers, school leaders, and parents, the study identifies difficulties in aligning the national Cambodian curriculum with Islamic values, teacher preparedness limitations, and student adaptation constraints. This research integrates literature reviews and presents a conceptual framework that illustrates the dual influence of national and religious curricula on classroom practices. The findings are organized into three key themes: curriculum integration, pedagogical implementation, and socio-cultural barriers. Tables are included to highlight data patterns and thematic insights. The study provides strategic recommendations to improve the synergy between moral instruction and academic goals in post-conflict educational settings.